Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

A GPC3 antigenic peptide based nanovaccine to potentiate immunotherapy of hepatocellular carcinoma - Yang Qin; Longtianyang Lei; Chaoyi Liu; Chonghao Liao; Zhenghao Tao; Yao Cheng; Qing Gao; Runshu Fu; Zhuoyi Rong; Haitao Zhang; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Climate change during the early Middle Jurassic: Evidence from coal-bearing strata of the Ordos Basin - Nian-De Shang; Jing-Jing Liu; Shi-Feng Dai; Ian T. Graham; Qiu-Chan Han; Rong-Kun Jia; Jia-Wei Feng; Meng-Da Yao; Yan Wang (Palaeoworld, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Estimation of the Hydrological Regime Variability Risk of a Regulated River - Chenguang Xiang; Wei Huang; Cuixia Yao; Le Luo; Rong Zhang; Jing Wang; Pan Yang (Water Resources Management, 2026)

Unravelling the migration of bioactive and volatile compounds coupled with water sublimation from grapes to recovered water during dynamic freeze-drying - Mengru Li; Wei Zhang; Yuan Huang; Xiaoying Zhang; Wuernisha Kadeer; Leihong Mao; Yuqian Jiang; Rong Tsao; Yao Tang (Food Chemistry, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Synergistic electrostatic, coordination, and redox mechanisms in cationic covalent organic frameworks for ultrafast and selective gold recovery - Meng-Yao Zhou; Xiu Wang; Shun-Hao Zeng; Qian-Qian Zhao; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Antibiotics shape the core microbial community distribution between floc and biofilm in an endogenous partial denitrification system: Insight from metabolic pathway - Kai-Yue Dong; Chao-Xi Yang; Jin-Luo Pang; Rong-Rong Chang; Ke-Yu Chen; Wei Yao; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Enhanced phosphate removal by lanthanum functionalization using zirconium-based metal organic frameworks: Role of in situ formed La(OH)3 - Suyu Kong; Meili Ding; Mengjiao Yu; Wei Rong; Yang Wang; Jianfeng Yao (Journal of Environmental Chemical Engineering, 2025)

Microwave-assisted pyrolysis of spent bleaching clay: A study of pyrolysis characteristics, kinetics, and intrinsic mechanism - Bang Yao; Li Chao; Yingwen Zhang; Yang Liu; Chunbao Zhou; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Lei Gao; Chen Chen; et al. (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Model-based analysis for investigating the impact of tumor size, lymphocyte and neutrophil on the survival of breast cancer 4T1 tumor-bearing mice - Qing-yu Yao; Xin-yu Hou; Wei-zhe Jian; Tian-yu Wang; Ping-yao Luo; Jun-sheng Xue; Rong Chen; Tian-yan Zhou (Toxicology and Applied Pharmacology, 2025)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Preliminary analysis of the indicators and accumulation models of gas hydrates in the central Zhongjiannan Basin, western South China sea - Zhou-rong Cai; Xin Sui; Yong-jian Yao; Zheng-xin Yin; Xiao-dong Yang; Dong Ju; Rong-wei Zhu; Xiao-xiang Wang; Huo-dai Zhang (Marine and Petroleum Geology, 2024)

Development of a loading and diagnostic system to study laboratory earthquakes - Rong Chen; Ying Xu; Xuan Li; Wei Yao; Sheng Huang; Qi Zhao (Bulletin of Engineering Geology and the Environment, 2024)

External redox couple enhanced anammox sludge activity at low temperature: Insight into intracellular resource synthesis - Rong-Rong Chang; Wei Yao; Jin-Luo Pang; Kai-Yue Dong; Yao-Yao Lu; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2024)

Evolution and disappearance of the paleo-West Pacific Anomaly: Implications to the future of South Atlantic Anomaly - Yaochen Yue; Jiawei Gao; Fei He; Yong Wei; Shuhui Cai; Huapei Wang; Yuqi Wang; Zhaojin Rong; Zhonghua Yao; Wei Lin; Yongxin Pan (Physics of the Earth and Planetary Interiors, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

Integrated analysis of natural glycans using a versatile pyrazolone-type heterobifunctional tag ANPMP - Yuxia Liu; Tong Yang; Jinqiao Rong; Jinhang Yuan; Lijuan Man; Ming Wei; Jiangbo Fan; Yao Lan; Yinchuan Liu; Guiping Gong; Yu Lu; Xuezheng Song; et al. (Carbohydrate Polymers, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Preparation of size-tunable Fe3O4 magnetic nanoporous carbon composites by MOF pyrolysis regulation for magnetic resonance sensing of aflatoxin B1 with excellent anti-matrix effect - Zhou Xu; Yanqiu Chen; Rong Wang; Maolong Chen; Jian Zhang; Yunhui Cheng; Bangben Yao; Li Yao; Jianguo Xu; Wei Chen (Food Chemistry, 2024)

Engineered hydrochar from waste reed straw for peroxymonosulfate activation to degrade quinclorac and improve solanaceae plants growth - Chunxia Ding; Can Ye; Wei Zhu; Guangyong Zeng; Xuemei Yao; Yu Ouyang; Jie Rong; Yaping Tao; Xiangying Liu; Yaocheng Deng (Journal of Environmental Management, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

Electrophilic components from Xiaoheiyao (rhizomes of Inula nervosa Wall.) alleviate the production of heterocyclic aromatic amines via creatinine inhibition - Xiang-Rong Cheng; Jia-Hui Ma; Issoufou Amadou; Wei Zhao; Yu-Yao Chen; Chen-Xi Zhang; Bin Guan (Food Chemistry, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Dual-functional electrostatic self-assembly nanoparticles enable suppressed defects and improved charge transport in perovskite optoelectronic devices - Hu Zhang; Pengfei Xu; Zhiliang Chen; Hengkai Zhang; Wenlong Shao; Yanhui Li; Jianfeng Yao; Da Rong; Duanwangde Liu; Liangpan Yang; Siliang Wang; Pengbin Gui; et al. (Chemical Engineering Journal, 2023)

Effects of synthetic astaxanthin and Haematococcus pluvialis on growth, antioxidant capacity, immune response, and hepato-morphology of Oncorhynchus mykiss under cage culture with flowing freshwater - Wei Zhao; Han-Lin Wei; Meng-Die Chen; Rong Yao; Zi-Qiao Wang; Jin Niu (Aquaculture, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Modification of TiO2 by Er3+ and rGO enhancing visible photocatalytic degradation of arsanilic acid - Xinghao Ren; Hang Yao; Rui Tang; Rong A; Shoujun Yuan; Wei Wang; Ibrahim Mohamed Ali; Zhen-Hu Hu (Environmental Science and Pollution Research, 2022)

Neural mechanisms underlying empathy during alcohol abstinence: evidence from connectome-based predictive modeling - Guanzhong Yao; Luqing Wei; Ting Jiang; Hui Dong; Chris Baeken; Guo-Rong Wu (Brain Imaging and Behavior, 2022)

Development of UPLC-MS/MS method for determining hainanmycin in foods of animal origin - Ke-xin Chi; Hang Yu; Ya-hui Guo; Yu-liang Cheng; Yun-fei Xie; Wei-rong Yao (Food Additives & Contaminants: Part A, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Ventromedial Thalamus-Projecting DCN Neurons Modulate Associative Sensorimotor Responses in Mice - Jie Zhang; Hao Chen; Li-Bin Zhang; Rong-Rong Li; Bin Wang; Qian-Hui Zhang; Liu-Xia Tong; Wei-Wei Zhang; Zhong-Xiang Yao; Bo Hu (Neuroscience Bulletin, 2022)

Influence of Notch Geometry on the Rock Fracture Toughness Measurement Using the ISRM Suggested Semi-Circular Bend (SCB) Method - Geli Zhao; Wei Yao; Xing Li; Ying Xu; Kaiwen Xia; Rong Chen (Rock Mechanics and Rock Engineering, 2022)

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Effects of Dietary Rhodobacter sphaeroides Protein Substitution of Fishmeal and Coenzyme Q10 Supplementation on Growth Performance, Intestinal Microbiota and Stress Tolerance of Litopenaeus vannamei in Acute Low Salinity - Zhihong Liao; Yangyang Gong; Ziqiao Wang; Yingjie Wang; Rong Yao; Mengdie Chen; Dan Wei; Wei Zhao; Xuanshu He; Jin Niu (Frontiers in Marine Science, 2022)
A 56-day culture experiment followed by an acute low salinity challenge was conducted to evaluate the effects of Rhodobacter sphaeroides protein (RSP) substitution of fishmeal and Coenzyme Q10 (CoQ10) supplementation on growth performance, intestinal microbiota and compressive capacity of Litopenaeus vannamei ( L. vanname i). Four experimental diets were formulated: FM diet (20% fishmeal), RSP diet (20% RSP instead of 20% fishmeal), CoQ10 diet (20% fishmeal supplemented with CoQ10 at 0.08 g kg –1 ), RSP + CoQ10 diet (20% RSP supplemented with CoQ10 at 0.08 g kg –1 ). The obtained results were denoted that L. vannamei fed CoQ10 diet could improve growth performance (weigh gain and specific growth rate), condition factor and crude lipid, and decrease hepatosomatic index, but no differences were found in survival rates. High throughput sequencing on intestinal microbiota indicated that intestinal microbiota of L. vannamei consisted mainly of Proteobacteria and Firmicutes . The species richness of the RSP diet was remarkably higher than that of the other diets. Moreover, the presence of RSP and CoQ10 may improve intestinal homeostasis by inhibiting the propagation of Vibrio . Compared to FM diet and RSP diet, supplementation of CoQ10 significantly improved the compressive capacity of L. vannamei against the acute low salinity challenge, as indicated by higher survival rates as well as higher activities of T-AOC and higher transcript levels of SOD , HSP70 , and Relish gene. Our findings demonstrated that RSP could serve as a novel FM and CoQ10 could serve as a prospective feed additive to help L. vannamei to overcome environmental stresses.

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Isolation of two sesquiterpene glycosides from Sapindus mukorossi Gaertn. with cytotoxic properties and analysis of their mechanism based on network pharmacology - Min-ping Wei; Xiao-wen Zhu; Hang Yu; Yun-fei Xie; Ya-hui Guo; Yu-liang Cheng; He Qian; Wei-rong Yao (Natural Product Research, 2021)

The effectiveness of extended binding affinity of prophage lysin PlyARI against Streptococcus suis infection - Yuyi Xiao; Rong Chen; Min Li; Zitai Qi; Yanfei Yu; Zihao Pan; Huochun Yao; Zhixin Feng; Wei Zhang (Archives of Microbiology, 2021)

Hippocampal Interneurons are Required for Trace Eyeblink Conditioning in Mice - Wei-Wei Zhang; Rong-Rong Li; Jie Zhang; Jie Yan; Qian-Hui Zhang; Zhi-An Hu; Bo Hu; Zhong-Xiang Yao; Hao Chen (Neuroscience Bulletin, 2021)
While the hippocampus has been implicated in supporting the association among time-separated events, the underlying cellular mechanisms have not been fully clarified. Here, we combined in vivo multi-channel recording and optogenetics to investigate the activity of hippocampal interneurons in freely-moving mice performing a trace eyeblink conditioning (tEBC) task. We found that the hippocampal interneurons exhibited conditioned stimulus (CS)-evoked sustained activity, which predicted the performance of conditioned eyeblink responses (CRs) in the early acquisition of the tEBC. Consistent with this, greater proportions of hippocampal pyramidal cells showed CS-evoked decreased activity in the early acquisition of the tEBC. Moreover, optogenetic suppression of the sustained activity in hippocampal interneurons severely impaired acquisition of the tEBC. In contrast, suppression of the sustained activity of hippocampal interneurons had no effect on the performance of well-learned CRs. Our findings highlight the role of hippocampal interneurons in the tEBC, and point to a potential cellular mechanism subserving associative learning.

Mucor rongii sp. nov., a New Cold-Tolerant Species from China - Feirong Bai; Su Yao; Chengshan Cai; Tianci Zhang; Yu Wang; Wei Liu; Baowen Ma; Changyuan Rong; Chi Cheng (Current Microbiology, 2021)

Long-term impact of accidental pollution on the distribution and risks of metals and metalloids in the sediment of the Longjiang River, China - Qian-Li Ma; Ling-Ai Yao; Qing-Wei Guo; Guang-Jie Zhou; Rong-Chang Liang; Qiao-Li Fang; Zhen-Cheng Xu; Xue-Min Zhao (Environmental Science and Pollution Research, 2021)

High resolution UPLC-MS/MS method for simultaneous separation and determination of six flavonoids from semen cuscutae extract in rat plasma: application to comparative pharmacokinetic studies in normal and kidney-deficient rats - Wei Zhang; Zhi-Tian Fu; Yao Xie; Zhi-Wen Duan; Yu Wang; Rong-Hua Fan (Natural Product Research, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Toxicity and metabolism of 3-bromopyruvate in Caenorhabditis elegans - Qiao-ling Gu; Yan Zhang; Xi-mei Fu; Zhao-lian Lu; Yao Yu; Gen Chen; Rong Ma; Wei Kou; Yong-mei Lan (Journal of Zhejiang University-SCIENCE B, 2020)

HL2 on chromosome 7D of wheat (Triticum aestivum L.) regulates both head length and spikelet number - Hongni Yao; Quan Xie; Shulin Xue; Jing Luo; Jikang Lu; Zhongxin Kong; Yongpan Wang; Wenling Zhai; Nan Lu; Rong Wei; Yang Yang; Yuzhou Han; et al. (Theoretical and Applied Genetics, 2019)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Pleiotropic effects of the wheat domestication gene Q on yield and grain morphology - Quan Xie; Na Li; Yang Yang; Yulong Lv; Hongni Yao; Rong Wei; Debbie L. Sparkes; Zhengqiang Ma (Planta, 2018)

A new pyridine alkaloid from Zingiberis rhizoma - Feng Shao; Ding-qing Wang; Wei Xiong; Pu-zhao Zhang; Guang-qiang Ma; Rong-hua Liu; Xue-lian Yao (Natural Product Research, 2017)

Copper-modified palygorskite is effective in preventing and treating diarrhea caused by Salmonella typhimurium - Da-wei Yao; Ze-zhong Yu; Na Li; Yu-nong Hou; Jia-rong Xu; De-ji Yang (Journal of Zhejiang University-SCIENCE B, 2017)

Dynamic Fracture Properties of Rocks Subjected to Static Pre-load Using Notched Semi-circular Bend Method - Rong Chen; Kang Li; Kaiwen Xia; Yuliang Lin; Wei Yao; Fangyun Lu (Rock Mechanics and Rock Engineering, 2016)

Hairy root induction and polysaccharide production of medicinal plant Callerya speciosa Champ. - Shao-chang Yao; Long-hua Bai; Zu-zai Lan; Mei-qiong Tang; Yong-jin Zhai; Hao Huang; Rong-chang Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

RETRACTED ARTICLE: Correlation of Promoter Methylation in the MGMT Gene with Glioma Risk and Prognosis: a Meta-Analysis - Xiang Dong; Rong-Yao Liu; Wei-Dong Chen (Molecular Neurobiology, 2015)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

The expression and functional role of a FOXC1 related mRNA-lncRNA pair in oral squamous cell carcinoma - Xiang-pan Kong; Jie Yao; Wei Luo; Fu-kui Feng; Jun-tao Ma; Yi-peng Ren; De-li Wang; Rong-fa Bu (Molecular and Cellular Biochemistry, 2014)

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Effect of a single-dose rifampin on the pharmacokinetics of pitavastatin in healthy volunteers - Yao Chen; Wei Zhang; Wei-hua Huang; Zhi-rong Tan; Yi-cheng Wang; Xi Huang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Use of reverse genetics to develop a novel marker porcine reproductive and respiratory syndrome virus - Tao Lin; Xiangrui Li; Huochun Yao; Zuzhang Wei; Feifei Tan; Runxia Liu; Lichang Sun; Rong Zhang; Wenliang Li; Jiaqi Lu; Guangzhi Tong; Shishan Yuan (Virus Genes, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

Development of a real-time RT-PCR method for rapid detection of H9 avian influenza virus in the air - Jing Lv; Baozhi Wei; Tongjie Chai; Xianzhu Xia; Zengmin Miao; Meiling Yao; Yuwei Gao; Rong Huang; Huili Yang; Uwe Roesler (Archives of Virology, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)